2020
DOI: 10.1002/batt.202000194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Charge Carrier Transport Toward Optimized Cathode Composites for All‐Solid‐State Li−S Batteries

Abstract: A high theoretical energy density makes lithium‐sulfur (Li−S) batteries promising candidates for energy storage systems of the post‐lithium‐ion generation. As the performance of Li−S cells with liquid electrolytes is impaired by the solubility of reaction intermediates, solid‐state cell concepts represent an auspicious approach for future electrochemical energy storage. However, the kinetics of Li−S solid‐state batteries and high charge/discharge rate still remain major challenges, and in‐depth knowledge of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 139 publications
(357 reference statements)
3
95
1
Order By: Relevance
“…The direct‐current polarization measurements of symmetric cells were conducted by reference to the previous report. [ 34 ] For electronic conductivity (σ el ), constant potentials of 5, −10, 20, and −30 mV were applied for 6 h for each potential. For ionic conductivity (σ ion ), constant potentials of 60 and −40 mV were applied for 12 h for each potential.…”
Section: Methodsmentioning
confidence: 99%
“…The direct‐current polarization measurements of symmetric cells were conducted by reference to the previous report. [ 34 ] For electronic conductivity (σ el ), constant potentials of 5, −10, 20, and −30 mV were applied for 6 h for each potential. For ionic conductivity (σ ion ), constant potentials of 60 and −40 mV were applied for 12 h for each potential.…”
Section: Methodsmentioning
confidence: 99%
“…As shown above, the synthesis of solid electrolytes via mechanochemical milling often leads to better ionic conductors, nevertheless, Dewald et al [ 168 ] have shown for Li 6 PS 5 Cl and Li 10 GeP 2 S 12 that the ionic conductivity decreases if the ampoule synthesized compound is further processed in the ball mill ( Figure 9 ). By investigating the compound by X‐ray diffraction, it was shown that the observed trends by rapid annealing and quenching are reversed when a crystalline compound is processed in the ball mill, where a significant amorphization occurs.…”
Section: The Influence Of Mechanochemical Processing Of Solid‐state Batteriesmentioning
confidence: 99%
“…However, the cathode tortuosity and processing have to be strongly adapted as intimate contact between the solid electrolyte and sulfur-carbon composite is crucial. [56] Polymeric electrolytes are easier to process but need to be run at elevated temperatures, leading to the partial dissolution of polysulfides and a charge/discharge behavior, which is known from state-of-the-art of ether electrolytes. [57] Further developments are, however, still required to enable Li-S technology to fulfil its potential.…”
Section: Limitationsmentioning
confidence: 99%